2020
DOI: 10.1558/cj.v26i2.246-266
|View full text |Cite
|
Sign up to set email alerts
|

Individual Learner Differences in CALL

Abstract: In Spring semester 2006, we conducted a study with 50 learners of German to investigate the use of a new measure (Cárdenas-Claros, 2005) for research on the field independent/dependent (FID) cognitive style and CALL use. After the measure was administered, students worked on a CALL program for German that logs interaction. This paper reports the reliability and item analysis of the FID-CALL measure in addition to its relationship with learners' behaviors in the CALL program. With the goal of understanding how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…Given that the effectiveness of information processing depends on what we already know, more attention needs to be afforded to supporting learners to develop their knowledge structures in long‐term memory as well as supporting them to build bridges to connect the old with the new knowledge (Tarchi, ). It has been suggested that instruction and environmental factors can lead to changes in FI (Murphy & Doucette, ), leading Chapelle and Heift () to argue that its effects reflected the interaction between the trait and the context. Witkin and Goodenough () acknowledged that some individuals exhibited a greater flexibility in style.…”
Section: Fi Preferred Learning Patterns and Performancementioning
confidence: 99%
“…Given that the effectiveness of information processing depends on what we already know, more attention needs to be afforded to supporting learners to develop their knowledge structures in long‐term memory as well as supporting them to build bridges to connect the old with the new knowledge (Tarchi, ). It has been suggested that instruction and environmental factors can lead to changes in FI (Murphy & Doucette, ), leading Chapelle and Heift () to argue that its effects reflected the interaction between the trait and the context. Witkin and Goodenough () acknowledged that some individuals exhibited a greater flexibility in style.…”
Section: Fi Preferred Learning Patterns and Performancementioning
confidence: 99%
“…Although the second-language acquisition (SLA) field has acknowledged the importance of individual learning differences in general (Ehrman, 2008;Skehan, 1991;Wakamoto, 2009), few studies have focused specifically on their role in L2 language development in CALL learning environments. Most studies have examined student-learning styles using a field independent/dependent (FID) construct (Chapelle & Jamieson, 2008;Chapelle & Heift, 2009). The following section will outline some of the most important findings from these studies, while demonstrating the need for exploring further and understanding more fully learner differences and preferences in the hybrid-learning environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, she argued that examining personality factors may tell us a more complete developmental story than only looking at proficiency measures because of the potential interactions with learner strategies (p.120). Chapelle & Heift (2009) have recently conducted research that highlights individual learner differences within the field of CALL. Specifically, they look at the individual learning style of Field Independence/Dependence (FID) and argue that these individual differences are not simply "traits" but should be understood within an interactionist construct that takes into consideration the individual and his/her interaction within the CALL context.…”
Section: (Insert Figure 1)mentioning
confidence: 99%
“…Cognitive changed refers to the development of new neural connections where learners are able to construct and confirm meaning (Setiani and Mackinnon, 2015). The concept of FD and FI in DE was also utilized by Chapelle and Heift (2013). They distinguished FI learners as self-directed, logical, analytical and independent.…”
Section: Forum Dosen Indonesiamentioning
confidence: 99%